The interaction between spiritual intelligence and self-compassion and their impact on personality traits among students at King Abdulaziz University in Jeddah (The International Journal of Educational Sciences and Arts, 2024)
The study aimed to reveal the interaction between spiritual intelligence and self-compassion and their impact on personality traits among students at King Abdulaziz University in Jeddah. The descriptive analytical method and the scale (spiritual intelligence, self-compassion, personality traits) were used as tools for the study, and were applied to a sample consisting of (383) Male and female students from King Abdulaziz University in Jeddah, the results of the study showed that there is a positive correlation between (spiritual intelligence and personality traits, self-compassion and personality traits, and spiritual intelligence And self-compassion), The results also showed that the effect of the interaction between spiritual intelligence and self-compassion On personality traits, it was very large for the study sample members, but spiritual intelligence was very large and most influential in the interaction on their personality traits, followed by the effect of self-compassion, which was also very large.
Keywords: Spiritual Intelligence; Self-Compassion; Personality Traits; Students